Fluoride solid electrolyte material, preparation method thereof and all-solid-state lithium battery
By introducing mixed anions and doped cations into fluoride solid electrolyte materials, adjusting their microstructure and ionic energy, the problem of existing halide solid electrolytes being easily oxidized at high voltages is solved, and high oxidation stability and High ionic conductivity improves the performance of all solid-state lithium batteries.
Patent Information
- Application Number
- CN202411491516.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
The existing halide solid electrolytes are easily oxidized at high voltages, resulting in serious interface side reactions, increasing interface impedance, reducing the capacity and life of lithium batteries. At the same time, its ionic conductivity is not ideal, limiting the capacity of all solid lithium batteries and Rate performance.
Fluoride solid electrolyte material is used, and its chemical formula is LiyY1-zMzF3-xXx. By introducing mixed anions and doped cations, the microstructure and ionic energy of the electrolyte are adjusted, and its oxidation stability and ionic conductivity are improved.
The high oxidation stability and high ionic conductivity of fluoride solid electrolyte materials at high voltages can be achieved, which can better match the oxide positive electrode materials with high oxidation potential, and improve the cycle stability and energy density of all-solid lithium batteries.
Smart Images

Figure CN119481245A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery electrolytes, and in particular relates to a fluoride solid electrolyte material and a preparation method thereof, and an all-solid-state lithium battery. Background Art
[0002] All-solid-state lithium batteries using solid electrolyte materials can overcome the limitations of existing lithium batteries in principle and are expected to become the next generation of energy storage systems. It solves some safety issues caused by the flammability of organic liquid electrolytes and has the potential to match lithium metal anodes and high-voltage cathode materials to provide higher energy density. Therefore, all-solid-state lithium batteries have significant advantages of high safety and high energy density. Among them, solid electrolyte materials are one of the key materials of all-solid-state lithium batteries and play a decisive role in battery performance.
[0003] The energy density and power density of lithium batteries are directly related to voltage. Therefore, increasing the voltage of the positive electrode material is of great significance for improving the energy density of lithium batteries and the power density at the same current density. + Around), good ionic conductivity at room temperature (10 -4 Up to 10 -3 S cm -1 ) and excellent cold compression deformation ability make it an excellent positive terminal solid electrolyte. However, as the voltage of the positive electrode material increases (>4V vs Li / Li + ), the common halide solid electrolyte will be oxidized, the interface compatibility will deteriorate, resulting in serious side reactions at the cathode-electrolyte interface, causing an increase in interface impedance, which will lead to a decrease in lithium battery capacity and a shortened lifespan. In addition, the ionic conductivity of common halide solid electrolytes is not ideal (usually <1mS·cm -1 ), leading to Li + The slow transmission limits the capacity and rate performance of all-solid-state lithium batteries.
[0004] For halide solid electrolytes, the ideal material should have very good oxidation stability and high ionic conductivity, but it is a challenge to achieve high voltage stability and high ionic conductivity of halide solid electrolytes at the same time. At present, the common positive end halide solid electrolytes are chlorides, such as Li3YCl6, Li3InCl6, Li2ZrCl6, etc. Chloride solid electrolytes are relatively + The oxidation potential is about 4V. If it is matched with LiNi 0.9 Co 0.05 Mn 0.05A strong side reaction will occur when a high voltage oxide such as O2 is used as the positive electrode (the oxidation potential of NCM955 is 4.35V). Theoretical calculations show that fluoride solid electrolytes are more effective than Li / Li + The oxidation potential of is above 6V, so replacing Cl with F, a more electronegative element, can effectively prevent the decomposition of halide electrolytes under high voltage and generate F-rich components in the cathode-electrolyte interphase (CEI), further inhibiting the occurrence of side reactions. However, the addition of F will enhance the interaction between the anion framework and Li + The interaction between the two species greatly reduces the ionic conductivity. For example, the traditional Li3YF6 fluoride solid electrolyte has strong oxidation stability, but its ionic conductivity is very low. Summary of the invention
[0005] Based on the above technical problems, the present invention provides a fluoride solid electrolyte material, a preparation method thereof and an all-solid-state lithium battery. The solid electrolyte material has very good oxidation stability and high ionic conductivity, and the preparation method is simple. It can match high-voltage positive electrode materials and improve the cycle performance and energy density of the all-solid-state lithium battery.
[0006] At present, the main method to improve the ionic conductivity of solid electrolyte materials is to regulate their macroscopic and microscopic structures, adjust the potential energy of ions at different sites in the solid, thereby reducing the activation energy during ion migration and increasing the rate of ion migration between different sites. The ion potential energy at different sites in the solid is mainly related to the surrounding chemical environment, including the type, distance and angle of the coordinated ions. The closer the distance, the greater the impact on its potential energy. For Li + Cations, the closest ions are usually anions, including O 2- , X - (F - , Cl - Br - ,I - ), S 2- When the type and amount of anions change, the corresponding site Li + The potential energy of the ions has a great influence. For example, when Li + When the ion is located in the tetrahedral gap, the surrounding coordinated ions are S 2- When Li + The ion potential energy is low, and when the coordinated ion becomes X - When halogen, Li + Therefore, on the one hand, the introduction of mixed anions can achieve the regulation of the potential energy of different sites, especially O 2- / X - , O 2- / S 2- , S 2- / X - Mixed anions are beneficial to reduce the Li + ion potential difference, thereby reducing Li + On the other hand, isovalent or heterovalent cation substitution strategies have been widely adopted to enhance the ionic conductivity of halide electrolytes. Cation substitution can adjust the Li + The ratio of vacancy concentration to the vacancy concentration broadens the ion transport path in the lattice, thus achieving Li + Fast transmission.
[0007] In view of this, the present invention proposes a fluoride solid electrolyte material, the chemical formula of the electrolyte material is: Li y Y 1-z M z F 3-x X x ;
[0008] Wherein, M is an element doped to replace Y, and X is an element doped to replace F; M is a Group IIIB and / or Group IVB element, and X is an oxygen-containing element.
[0009] In the present invention, the fluoride solid electrolyte material is essentially modified based on the halide solid electrolyte matrix material YF3. Figure 1 It can be seen that when YF3 is used as the main framework, this type of solid electrolyte has an open cubic structure. Li is introduced into the structure through solid phase reaction. + , while doping a certain amount of oxygen-containing anions (such as O 2- ) replaces part F - , F - The high-voltage stability of the electrolyte is enhanced, and O 2- Stabilize Li + The coplanar octahedral transmission channel broadens the Li + transmission path, weakening the F - adverse effect on ionic conductivity; further, group IIIB and / or group IVB element cations (such as La 3+ 、Ce 3+ 、Zr 4+ ) replace part Y 3+ , regulating the Li + The energy of the sites and the thermodynamic stability of the electrolyte can further improve the ionic conductivity. Finally, the fluoride solid electrolyte of the present invention has both good high voltage stability and high ionic conductivity, which can better match the oxide positive electrode material with high oxidation potential, and improve the cycle stability and energy density of the all-solid-state battery.
[0010] Preferably, M is at least one of La, Ce or Zr, and X is O.
[0011] In the present invention, M may also be Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, Hf or Rf, and X may also be S.
[0012] Preferably, 0.5≤x≤1, 0.5≤y≤1, 0≤z≤0.5; for example, x may be 0.5, 0.6, 0.7, 0.8, 0.9, 1, y may be 0.5, 0.6, 0.7, 0.8, 0.9, 1, and z may be 0.1, 0.2, 0.3, 0.4, 0.5.
[0013] Preferably, x=y.
[0014] In the present invention, x is a coefficient for adjusting F and the oxygen-containing element X. By limiting x, the amount of F occupied by X (i.e., the oxygen-containing element) in LiYF3 can be controlled. The amount of F occupied by X (i.e., the oxygen-containing element) is a key factor in regulating the ionic conductivity and high-voltage stability of the LiYF3 solid electrolyte. Experiments have shown that controlling the value of x to be 0.5-1 can optimize the performance of the doped fluoride solid electrolyte material. Similarly, y is a coefficient for adjusting the lithium-poor state and the lithium-rich state. By adjusting the value of y, the lithium content of the doped halide solid electrolyte can be adjusted to achieve the lithium-poor state (i.e., The regulation between the high lithium ion vacancy number (i.e., the lithium-rich state) and the lithium-rich state (i.e., the high lithium ion concentration) is experimentally proved that when the value of y is controlled to be 0.5-1, the oxidation stability and ionic conductivity of the fluoride solid electrolyte material can also be optimized; in addition, z is a coefficient for adjusting Y and M. By limiting z, the amount of M occupied by Y in LiYF3 can be controlled, and the energy of the corresponding site and the thermodynamic stability of the electrolyte can be adjusted. Experiments have shown that when z is controlled not to exceed 0.5, the ionic conductivity of the doped fluoride solid electrolyte material can be further improved.
[0015] Preferably, the chemical formula of the electrolyte material is at least one of the following:
[0016] LiYF2O、Li 0.7 YF 2.3 O 0.7 , Li 0.8 Y 0.7 La 0.3 F 2.2 O 0.8 , Li 0.7 Y 0.6 Ce 0.4 F 2.3 O 0.7 , Li 0.8 Y 0.8 Zr0.2 F 2.4 O 0.8 , Li 0.8 Y 0.5 La 0.3 Zr 0.2 F 2.4 O 0.8 .
[0017] The present invention also provides a method for preparing the above-mentioned fluoride solid electrolyte material, comprising the following steps:
[0018] S1. Prepare the raw materials according to the general chemical formula Li y Y 1-z M z F 3-x X x The components and molar ratios shown are mixed and ball-milled to obtain a precursor;
[0019] S2. Solid-phase sintering the precursor under an inert atmosphere to obtain the fluoride solid electrolyte material.
[0020] Preferably, in step S1, the raw material includes fluorides or oxides of Li, Y, and M;
[0021] Preferably, the raw materials include yttrium fluoride, lithium oxide and M fluoride, and the lithium oxide is preferably at least one of lithium hydroxide, lithium oxide or lithium carbonate.
[0022] Preferably, in step S1, the ball milling medium used in the ball milling is zirconium oxide, and the dispersion medium is anhydrous ethanol;
[0023] Preferably, the ball-to-material ratio is 1-10:1, the ball milling speed is 200-800r / min, and the ball milling time is 1-20h. For example, the ball-to-material ratio can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, the ball milling speed can be 200rpm, 225rpm, 250rpm, 375rpm, 400rpm, 425rpm, 450rpm, 475rpm, 500rpm, 525rpm, 550rpm, 575rpm, 600rpm, 650rpm, 775rpm, 800rpm; the grinding time can be 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h.
[0024] Preferably, in step S1, the raw material further comprises a crown ether complex of Li;
[0025] Preferably, the crown ether complex of Li is obtained by a coordination reaction between a metal salt of Li and a crown ether, and the crown ether is a crown ether containing a hydroxyl group;
[0026] Preferably, when the raw material includes a crown ether complex of Li, the method further includes purifying and sintering the fluoride solid electrolyte material in an oxygen-containing atmosphere to obtain a final fluoride solid electrolyte material.
[0027] In the present invention, the hole structure of the crown ether has an effective complexing effect on Li ions. When the crown ether complex of Li is used as a raw material, during the ball milling process, the hydroxyl groups on the crown ether containing hydroxyl groups and yttrium fluoride form hydrogen bonds, Lewis acid-base interactions, etc., thereby forming a complex ion mixture. The complex ion mixture has a variety of coordination polyhedrons, which is beneficial to Y 3+ The rapid conduction of M ions ensures the effective doping of various ions, thereby further improving the ionic conductivity of the fluoride solid electrolyte material. Thereafter, through further purification and sintering, the crown ether containing hydroxyl groups is removed in a high-temperature oxygen atmosphere to obtain a fluoride solid electrolyte material with higher ionic conductivity.
[0028] Preferably, in step S2, the solid-phase sintering temperature is 500-700°C, and the time is 2-8h. For example, the solid-phase sintering temperature can be 520°C, 550°C, 580°C, 600°C, 630°C, 650°C, 670°C, or 700°C; and the time can be 2h, 3h, 4h, 5h, 6h, 7h, or 8h.
[0029] The present invention also provides an all-solid-state lithium battery, comprising a positive electrode active material, a negative electrode active material and an electrolyte material;
[0030] Wherein, the electrolyte material is the above-mentioned solid electrolyte material, or the solid electrolyte material prepared by the above-mentioned preparation method.
[0031] In the present invention, the positive electrode active material can be at least one of lithium cobalt oxide and its modified materials, lithium iron phosphate and its modified materials, lithium manganese iron phosphate and its modified materials, lithium nickel cobalt manganese oxide and its modified materials, lithium nickel cobalt aluminum oxide and its modified materials, lithium nickel oxide and its modified materials, lithium manganese oxide and its modified materials, lithium titanate, sulfur, selenium, and tellurium; the modified materials of the above-mentioned positive electrode active materials can be at least one of the positive electrode active materials that are doped and / or surface-coated.
[0032] The positive electrode active material may include but is not limited to LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (abbreviated as NCM523), LiNi 0.5 Co 0.25Mn 0.25 O2 (abbreviated as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM622), Li Ni 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM811), LiNi 0.96 Co 0.02 Mn 0.02 O2 (abbreviated as Ni96), LiNi 0.80 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and their respective modified materials.
[0033] The negative electrode active material can be at least one of graphite, graphene, carbon nanotubes, mesophase microcarbon beads, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, metal oxides, metallic lithium, lithium alloys, and lithium composite materials.
[0034] In the all-solid-state lithium battery provided by the present invention, the electrolyte is preferably provided in the form of an electrolyte layer.
[0035] Compared with the prior art, the present invention has the following technical effects:
[0036] The fluoride solid electrolyte material of the present invention starts with the composition and microstructure design of the electrolyte, by doping cationic metal elements and O elements of appropriate types and proportions, and by adjusting the ratio of anions to cations, a Li-YFO solid electrolyte with high oxidation stability and high ionic conductivity is generated. Compared with the original matrix material, the Li-YFO solid electrolyte has better ionic conductivity performance, which is conducive to its practical application in all-solid-state batteries, and realizes stable battery circulation and high energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the structure of YF3 solid electrolyte and its lithium ion migration channel;
[0038] Figure 2 is the EIS curve of the fluoride solid electrolyte material described in Examples 1-6;
[0039] Figure 3 A schematic diagram of the structure of an all-solid-state lithium battery assembled in an experimental example of the present invention;
[0040] Figure 4 The battery cycle performance diagram of the all-solid-state lithium battery assembled in the experimental example of the present invention at 1C;
[0041] Figure 5The charge and discharge curve of the all-solid-state lithium battery assembled in the experimental example of the present invention at 1C;
[0042] Figure 6 This is a rate performance test diagram of the all-solid-state lithium battery assembled in the experimental example of the present invention. DETAILED DESCRIPTION
[0043] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments, but it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0044] Example 1
[0045] This embodiment provides a fluoride solid electrolyte material, the general chemical formula of which is LiYF2O, and the preparation method thereof specifically comprises the following steps:
[0046] (1) LiOH and YF3 were weighed and mixed in a molar ratio of 1:1 and then loaded into a polytetrafluoroethylene ball mill. Anhydrous ethanol was added and ball milled using zirconium oxide balls as the ball milling medium. The ball-to-material mass ratio was 5:1. The ball milling speed was 500 r / min and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100°C and dried to obtain a black powder.
[0047] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0048] Example 2
[0049] This embodiment provides a fluoride solid electrolyte material, the chemical formula of which is: Li 0.7 YF 2.3 O 0.7 , and its preparation method specifically comprises the following steps:
[0050] (1) LiOH and YF3 were weighed and mixed in a molar ratio of 7:10, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconium oxide balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100°C for drying to obtain a black powder;
[0051] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0052] Example 3
[0053] This embodiment provides a fluoride solid electrolyte material, the chemical formula of which is: Li 0.8 Y 0.7 La 0.3 F 2.2 O 0.8 , and its specific preparation method comprises the following steps:
[0054] (1) LiOH, YF3 and LaF3 were weighed and mixed in a molar ratio of 8:7:3, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconium oxide balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100° C. and dried to obtain a black powder;
[0055] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0056] Example 4
[0057] This embodiment provides a fluoride solid electrolyte material, the chemical formula of which is: Li 0.7 Y 0.6 Ce 0.4 F 2.3 O 0.7 , and its specific preparation method comprises the following steps:
[0058] (1) LiOH, YF3 and CeF3 were weighed and mixed in a molar ratio of 7:6:4, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconia balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100° C. and dried to obtain a black powder;
[0059] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0060] Example 5
[0061] This embodiment provides a fluoride solid electrolyte material, the chemical formula of which is: Li 0.8 Y 0.8 Zr 0.2 F 2.4 O 0.8 , and its specific preparation method comprises the following steps:
[0062] (1) LiOH, YF3, and ZrF4 were weighed and mixed in a molar ratio of 8:8:2, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconium oxide balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100° C. and dried to obtain a black powder;
[0063] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0064] Example 6
[0065] This embodiment provides a fluoride solid electrolyte material, the chemical formula of which is: Li 0.8 Y 0.5 La 0.3 Zr 0.2 F 2.4 O 0.8 , and its specific preparation method comprises the following steps:
[0066] (1) LiOH, YF3, LaF3, and ZrF4 were weighed and mixed in a molar ratio of 8:5:3:2, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconium oxide balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100° C. and dried to obtain a black powder;
[0067] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0068] Example 7
[0069] This embodiment provides a fluoride solid electrolyte material, the chemical formula of which is: Li 1.5 YF 1.5 O 1.5 , and its preparation method specifically comprises the following steps:
[0070] (1) LiOH and YF3 were weighed and mixed in a molar ratio of 1.5:1, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconium oxide balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100°C for drying to obtain a black powder;
[0071] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0072] Example 8
[0073] This embodiment provides a fluoride solid electrolyte material, the chemical formula of which is: Li 0.8 Y 0.3 La 0.7 F 2.2 O 0.8 , and its preparation method specifically comprises the following steps:
[0074] (1) LiOH, YF3 and LaF3 were weighed and mixed in a molar ratio of 8:3:7, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconium oxide balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100° C. and dried to obtain a black powder;
[0075] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0076] Example 9
[0077] This embodiment provides a fluoride solid electrolyte material, the general chemical formula of which is LiYF2O, and the preparation method thereof specifically comprises the following steps:
[0078] (1) The crown ether complex of Li and YF3 were weighed and mixed according to the molar ratio of Li:Y of 1:1, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconium oxide balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100°C for drying to obtain a black powder;
[0079] The crown ether complex of Li is prepared by adding Li2CO3 and 2-hydroxymethyl-18-crown-6 into ethanol in a molar ratio of 1:2, ultrasonically dispersing for 2 hours, centrifuging, and vacuum drying to obtain the crown ether complex of Li;
[0080] (2) placing the black powder into a tube furnace and performing solid phase sintering in an argon atmosphere at a temperature of 500° C. for 5 h, cooling and taking out the powder, and then grinding the powder sufficiently to obtain a fluoride solid electrolyte material precursor;
[0081] (3) The fluoride solid electrolyte material precursor is placed in a tubular furnace again, purified and sintered in an air atmosphere at a temperature of 600° C. for 12 h. After cooling and taking out, the fluoride solid electrolyte material is obtained.
[0082] Comparative Example 1
[0083] This comparative example proposes a fluoride solid electrolyte material, the general chemical formula of which is Li3YF6, and the preparation method thereof specifically comprises the following steps:
[0084] (1) LiF and YF3 were weighed and mixed in a molar ratio of 3:1 and then loaded into a polytetrafluoroethylene ball mill. Anhydrous ethanol was added and ball milled using zirconium oxide balls as the ball milling medium. The ball-to-material mass ratio was 5:1. The ball milling speed was 500 r / min and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100°C and dried to obtain a black powder.
[0085] (2) The black powder is placed in a tubular furnace and solid-phase sintered in an argon atmosphere at a temperature of 500° C. for 5 h. After cooling and taking out, the powder is fully ground to obtain the fluoride solid electrolyte material.
[0086] Comparative Example 2
[0087] This comparative example proposes a fluoride solid electrolyte material, the general chemical formula of which is LiYF2O, and the preparation method thereof specifically comprises the following steps:
[0088] (1) The crown ether complex of Li and YF3 were weighed and mixed according to the molar ratio of Li:Y of 1:1, and then loaded into a polytetrafluoroethylene ball mill, anhydrous ethanol was added, and zirconium oxide balls were used as ball milling media for ball milling. The ball-to-material mass ratio was 5:1, the ball milling speed was 500 r / min, and the ball milling time was 10 h. After completion, the obtained slurry was placed in a vacuum oven at 100°C for drying to obtain a black powder;
[0089] The crown ether complex of Li is prepared by adding Li2CO3 and 18-crown-6 into ethanol at a molar ratio of 1:2, ultrasonically dispersing for 2 hours, centrifuging, and vacuum drying to obtain the crown ether complex of Li;
[0090] (2) placing the black powder into a tube furnace and performing solid phase sintering in an argon atmosphere at a temperature of 500° C. for 5 h, cooling and taking out the powder, and then grinding the powder sufficiently to obtain a fluoride solid electrolyte material precursor;
[0091] (3) The fluoride solid electrolyte material precursor is placed in a tubular furnace again, purified and sintered in an air atmosphere at a temperature of 600° C. for 12 h. After cooling and taking out, the fluoride solid electrolyte material is obtained.
[0092] Experimental example:
[0093] The fluoride solid electrolyte materials described in the above examples and comparative examples were subjected to EIS and activation energy tests, as follows:
[0094] The fluoride solid electrolyte material described in the embodiment or comparative example was poured into a polytetrafluoroethylene mold with a diameter of 12 mm and pressed into a sheet. Stainless steel current collectors were installed at both ends and sealed with sealant to ensure that the electrolyte would not contact the air. The above operations were all carried out in an argon environment. The electrochemical impedance spectroscopy (EIS) of the electrolyte at different temperatures was measured using a Biologic electrochemical workstation. The results are shown in FIG. Figure 2 See Figure 2 It can be seen that the conductivity of the fluoride solid electrolyte materials described in Examples 1-6 is large.
[0095] The fluoride solid electrolyte material described in Example 2 is assembled into a full battery, and the specific steps are as follows:
[0096] Preparation of positive electrode: The positive electrode active material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2)、Li 0.7 YF 2.3 O 0.7 (LYFO) and conductive agent SP were mixed in a mass ratio of 7:3:0.5, and then ball-milled in a planetary ball mill at a speed of 200 rpm for 30 min using a stainless steel ball mill to obtain a positive electrode;
[0097] Preparation of negative electrode: After laminating the metal lithium sheet and the metal indium sheet, press them on a tablet press at a pressure of 20 MPa for 10 hours to obtain a lithium-indium alloy negative electrode;
[0098] Assembly of full battery: refer to Figure 3 , based on the above NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2)、Li 0.7 YF 2.3 O 0.7 A mixture of (LYFO) and conductive agent SP is used as the positive electrode, lithium indium alloy is used as the negative electrode, LYFO and Li6PS5Cl (LPSC) are used as electrolytes, and they are pressed into sheets in a polytetrafluoroethylene mold with a diameter of 12 mm to form a full battery.
[0099] The battery was tested using the Xinwei battery testing system, with a charge and discharge voltage range of 2.8-4.5V. The battery was activated at a rate of 0.1C for three cycles and then cycled at a rate of 1C. The rate test was performed with 0.1C, 0.5C, 1C, 2C, 5C, and 0.1C currents for 5 cycles each. The results are as follows: Figure 4-6 See Figure 4-6 It can be seen that the fluoride solid electrolyte material described in the embodiment can enable the all-solid-state battery to have high capacity, high first coulombic efficiency and good cycle stability.
[0100] The conductivity and activation energy of the fluoride solid electrolyte materials in the embodiments and comparative examples are shown in Table 1 below:
[0101] Table 1 Electrical properties of the fluoride solid electrolyte materials described in Examples and Comparative Examples
[0102]
[0103]
[0104] As can be seen from Table 1 above, the embodiments of the present application significantly improve the ionic conductivity compared to the undoped solid electrolyte material by doping cationic metal elements and O elements of appropriate types and proportions.
[0105] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A fluoride solid electrolyte material, characterized in that: The general chemical formula of the electrolyte material is: Li y Y 1- z M z F 3-x X x ; Wherein, M is an element doped to replace Y, and X is an element doped to replace F; M is a Group IIIB and / or Group IVB element, and X is an oxygen-containing element.
2. The fluoride solid electrolyte material according to claim 1, characterized in that: M is at least one of La, Ce or Zr, and X is O.
3. The fluoride solid electrolyte material according to claim 1 or 2, characterized in that: 0.5≤x≤1, 0.5≤y≤1, 0≤z≤0.5; Preferably, x=y.
4. The fluoride solid electrolyte material according to any one of claims 1 to 3, characterized in that: The chemical formula of the electrolyte material is at least one of the following: LiYF2O、Li 0.7 YF 2.3 O 0.7 , Li 0.8 Y 0.7 La 0.3 F 2.2 O 0.8 , Li 0.7 Y 0.6 Ce 0.4 F 2.3 O 0.7 , Li 0.8 Y 0.8 Zr 0.2 F 2.4 O 0.8 , Li 0.8 Y 0.5 La 0.3 Zr 0.2 F 2.4 O 0.8 .
5. A method for preparing the fluoride solid electrolyte material according to any one of claims 1 to 4, characterized in that: The steps include: S1. Prepare the raw materials according to the general chemical formula Li y Y 1-z M z F 3-x X x The components and molar ratios shown are mixed and ball-milled to obtain a precursor; S2. Solid-phase sintering the precursor under an inert atmosphere to obtain the fluoride solid electrolyte material.
6. The method for preparing the fluoride solid electrolyte material according to claim 5, characterized in that: In step S1, the raw material includes fluoride or oxide of Li, Y, and M; Preferably, the raw materials include yttrium fluoride, lithium oxide and M fluoride, and the lithium oxide is preferably at least one of lithium hydroxide, lithium oxide or lithium carbonate.
7. The method for preparing the fluoride solid electrolyte material according to claim 5 or 6, characterized in that: In step S1, the ball milling medium used in the ball milling is zirconium oxide, and the dispersion medium is anhydrous ethanol; Preferably, the ball-to-material ratio is 1-10:1, the ball milling speed is 200-800 r / min, and the ball milling time is 1-20 h.
8. The method for preparing the fluoride solid electrolyte material according to claim 6 or 7, characterized in that: In step S1, the raw material further comprises a crown ether complex of Li; Preferably, the crown ether complex of Li is obtained by a coordination reaction between a metal salt of Li and a crown ether, and the crown ether is a crown ether containing a hydroxyl group; Preferably, when the raw material includes a crown ether complex of Li, the method further includes purifying and sintering the fluoride solid electrolyte material in an oxygen-containing atmosphere to obtain a final fluoride solid electrolyte material.
9. The method for preparing the fluoride solid electrolyte material according to any one of claims 6 to 8, characterized in that: In step S2, the solid phase sintering temperature is 500-700°C and the time is 2-8h.
10. An all-solid-state lithium battery, characterized in that: including positive electrode active materials, negative electrode active materials and electrolyte materials; Wherein, the electrolyte material is the solid electrolyte material according to any one of claims 1 to 4, or the solid electrolyte material prepared by the preparation method according to any one of claims 5 to 9.
Citation Information
Cited By
Semi-solid-state battery positive electrode slurry, semi-solid-state positive plate and semi-solid-state battery
CN120527390A